Physical processes in magnetic-pulse influence on thin-walled metals - Argun, Sh.; Snurnіkova, D.; Chernov, K.; Аргун, Щ. В.; Снурнікова, Д. А.; Чернов, К. В.; Снурникова, Д. А. (Харківський національний автомобільно-дорожній університет, 2014)
The inductor system to apply the purposeful magnetic pulse force to the inner cavity of the flat angle in the crook of a metal sheet with a quite high specific electrical conductivity is considered in the paper.
Фізичні процеси при магнітно-імпульсному впливі на тонкостінні метали
Физические процессы при магнитно-импульсном воздействии на тонкостенные металлы
Keywords: inductor system; electrical conductivity; electrical magnetic treatment of metal; індукторна система; питома електропровідність; магнітно-імпульсна обробка металів; индукторная система; удельная электропроводность; магнитно-импульсная обработка металлов; 621.318